173k views
3 votes
Please solve this and show explanation! ty!

Please solve this and show explanation! ty!-example-1
User Deepstop
by
5.0k points

2 Answers

0 votes

Answer: x=1 or x=−1

Step-by-step explanation: Step 1: Add 6 to both sides.

x2−6+6=−5+6

x2=1

Step 2: Take the square root.

x=±√1

BRAINLESS

User Thibault Deheurles
by
5.2k points
4 votes

Answer:

Explanation:

a.) c = 9

To get a perfect square you must divide the bx or 6x in this situation then square it.

6/2 = 3

3^2 = 9

b.) (x - 1)(x - 5)

x^2 - 6x + 9 = -5 + 9

x^2 - 6x + 9 = 4

x^2 - 6x + 9 - 4 = 4 - 4

x^2 - 6x + 5 = 0

(x - 1)(x - 5)

x - 1 = 0

x = 1

x - 5 = 0

x = 5

User Nayakam
by
5.4k points